Phoenicians and the Making of the Mediterranean - Lόpez-Ruiz, Carolina, 19??- (Cambridge, Mass. ; London)
426 sayfa
Keywords: “Long before Greeks dominated the ancient Mediterranean, Phoenicians were the lords of the sea. Setting out from their Levantine cities, they introduced their alphabet, art, technology, and gods to places as far as off as Iberia. Carolina López-Ruiz highlights the enduring Phoenician imprint, displacing the Hellenocentric model of the ancient World” --